Health-related quality of life and self-reported health status in adolescents with chronic health conditions before transfer of care to adult health care: an international cohort study - Mira Kallio; Anna Tornivuori; Päivi J. Miettinen; Kaija-Leena Kolho; Heikki Relas; Evelyn Culnane; Hayley Loftus; Susan M. Sawyer; Silja Kosola (BMC, 2024)
Abstract Background Heath-related quality of life (HRQoL) is lower in adolescents with chronic health conditions compared to healthy peers. While there is evidence of some differences according to the underlying condition and gender, differences by measure and country are poorly understood. In this study we focus on the differences in HRQoL in adolescents with various chronic medical conditions in the year before transfer of care to adult health services. We also study the associations of two different HRQoL measurements to each other and to self-reported health. Methods We recruited 538 adolescents from New Children`s Hospital, Helsinki, Finland, and the Royal Children`s Hospital, Melbourne, Australia in 2017-2020. We used two validated HRQoL measurement instruments, Pediatric Quality of Life Inventory (PedsQL) and 16D, and a visual analog scale (VAS) for self-reported health status. Results In total, 512 adolescents (50.4% female, mean age 17.8 [SD 1.2] years), completed the survey measures. Higher HRQoL was reported in males than females in both countries (PedsQL 79.4 vs. 74.1; 16D 0.888 vs. 0.846), and in adolescents from Finland than Australia (80.6 vs. 72.2 and 0.905 vs. 0.825, p < 0.001 for all). Adolescents with diabetes, rheumatological, nephrological conditions and/or organ transplants had higher HRQoL than adolescents with neurological conditions or other disease syndromes (p < 0.001). PedsQL and 16D scores showed a strong correlation to each other (Spearman correlation coefficient r = 0.81). Using the 7-point VAS (1-7), 52% (248 of 479) considered their health status to be good (6-7) and 10% (48 of 479) rated it poor (1-2). Better self-reported health was associated with higher HRQoL. Conclusions The HRQoL of transition aged adolescents varies between genders, diagnostic groups, and countries of residence. The association between self-reported health and HRQoL suggests that brief assessment using the VAS could identify adolescents who may benefit from in-depth HRQoL evaluation. Trial registration Trial registration name The Bridge and registration number NCT04631965 ( https://clinicaltrials.gov/ct2/show/NCT04631965 ).